Barrier Mechanisms in the Developing Brain - Saunders, Norman R.; Liddelow, Shane A.; Dziegielewska, Katarzyna M. (Frontiers in Pharmacology, 2012)
The adult brain functions within a well-controlled stable environment, the properties of which are determined by cellular exchange mechanisms superimposed on the diffusion restraint provided by tight junctions at interfaces between blood, brain and cerebrospinal fluid (CSF). These interfaces are referred to as “the” blood-brain barrier. It is widely believed that in embryos and newborns, this barrier is immature or “leaky”, rendering the developing brain more vulnerable to drugs or toxins entering the fetal circulation from the mother. New evidence shows that many adult mechanisms, including functionally effective tight junctions are present in embryonic brain and some transporters are more active during development than in the adult. Additionally, some mechanisms present in embryos are not present in adults, e.g. specific transport of plasma proteins across the blood-CSF barrier and embryo-specific intercellular junctions between neuroependymal cells lining the ventricles. However developing cerebral vessels appear to be more fragile than in the adult. Together these properties may render developing brains more vulnerable to drugs, toxins and pathological conditions, contributing to cerebral damage and later neurological disorders. In addition, after birth loss of protection by efflux transporters in placenta may also render the neonatal brain more vulnerable than in the fetus.